2021
DOI: 10.1097/ico.0000000000002694
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb Epithelial Edema Associated With Rho Kinase Inhibition: A Case Series and Review of the Literature

Abstract: The Rho kinase inhibitor netarsudil is a recently approved therapeutic option for the management of increased intraocular pressure in the United States. Although phase 3 clinical trials noted corneal changes related to the medication-namely, nonvisually-significant corneal verticillata-descriptions of a unique form of cystic epithelial edema began to surface as netarsudil (and its sister drug ripasudil, approved in Japan) gained widespread use. This series adds 3 new cases and reviews the current literature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…[ 20 ] Previous authors have described preexisting corneal edema as a risk factor for the occurrence of RECE. [ 14 15 16 17 18 ] All but two patients (one by Moumneh et al . [ 14 ] and one by Wisely et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 20 ] Previous authors have described preexisting corneal edema as a risk factor for the occurrence of RECE. [ 14 15 16 17 18 ] All but two patients (one by Moumneh et al . [ 14 ] and one by Wisely et al .…”
Section: Discussionmentioning
confidence: 99%
“…The decline in VA was the only significant symptom reported in all previous reports describing RECE. [ 14 15 16 17 18 ] No other symptoms associated with bullae have been reported. In our study, we found additional symptoms of foreign body sensation, eye pain, and ocular surface discomfort attributable to bullae in five eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More reports feature in recent literature on the topical use of netarsudil 0.02% (Rho-Kinase inhibitor and norepinephrine transport inhibitor), causing macrocellular reticular pattern of epithelial edema in eyes with pre-existing stromal edema and raised intraocular pressure. [ 2 3 4 5 6 7 8 ] This unique pattern of edema has been observed in the clinical setting of pre-existing endothelial cell dysfunction when netarsudil is used. Rho-kinase (ROCK) inhibitors regulate and increase the permeability of tight junctions, thereby permitting fluid movement from the corneal stroma to the epithelium.…”
mentioning
confidence: 93%
“…Watering of the eyes, corneal staining, and blurred or reduced vision are other side effects being less observed or reported. [ 2 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%